Exaining the Relationship Between University Students' Burnout, Social Support and Psychological Well-Being and Their Tendency to Involuntary Procrastination - Tarsuslu, Sinan (Fırat University, 2024)
This research was carried out to determine the relationship and the direction of the relationship between burnout levels, social support perceptions and psychological well-being of university students and their involuntary procrastination tendencies. For this purpose, the scales in the relevant literature were used. In addition, a descriptive-relationship-seeking type of research was preferred in this study. The study was carried out by reaching 328 students out of 1376 students studying at the health services vocational school of a university. In the research, proportional stratified sampling method was used to reduce sampling errors and to create samples with higher representativeness. In line with the research data, a moderate positive relationship was found between students' burnout levels and involuntary procrastination tendencies, a weak negative relationship between their perceived social support perceptions and involuntary procrastination tendencies, and a moderate negative relationship between their psychological well-being and involuntary procrastination tendencies. According to the results of the regression analysis between the variables, it was concluded that the burnout level, perceived social support and psychological well-being of the students had a significant effect on the involuntary procrastination tendency. As a result, it is thought that the research will contribute to a better understanding of the underlying causes of involuntary procrastination behaviour, which is an important factor affecting students‘ academic achievement in the field of educational psychology, and will provide an important tool for the development of programs to increase students’ motivation.

Bu araştırma, üniversite öğrencilerinin tükenmişlik düzeyleri, sosyal destek algıları ve psikolojik iyi oluş durumları ile istemsiz erteleme eğilimleri arasındaki ilişkileri ve ilişki yönünü belirlemek amacıyla gerçekleştirilmiştir. Bu amaç doğrultusunda ilgili literatürde yer alan ölçekler kullanılmıştır. Ayrıca bu çalışmada tanımlayıcı-ilişki arayıcı türde bir araştırma tipi tercih edilmiştir. Çalışma Erzincan Binali Yıldırım Üniversitesi sağlık hizmetleri meslek yüksekokulunda eğitim gören 1376 öğrenciden 328 kişiye ulaşılarak gerçekleştirilmiştir. Araştırmada örnekleme hatalarını azaltmak ve daha yüksek temsil yeteneğine sahip örneklemler oluşturmak için orantılı tabakalı örnekleme yöntemi kullanılmıştır. Araştırma verileri doğrultusunda öğrencilerin, tükenmişlik düzeyleri ile istemsiz erteleme eğilimleri arasında orta düzeyde pozitif bir ilişki, algıladıkları sosyal destek algıları ile istemsiz erteleme eğilimleri arasında negatif yönlü zayıf bir ilişki, psikolojik iyi oluşları ile istemsiz erteleme eğilimleri arasında negatif yönlü orta düzeyde bir ilişki tespit edilmiştir. Değişkenler arası yapılan regresyon analizi sonucuna göre de öğrencilerin tükenmişlik düzeyinin, algılanan sosyal desteğin ve psikolojik iyi oluşunun istemsiz erteleme eğilimi üzerinde anlamlı bir etkisinin olduğu sonucuna da ulaşılmıştır. Sonuç olarak, araştırma eğitim psikolojisi alanında öğrencilerin akademik başarısını etkileyen önemli bir faktör olan istemsiz erteleme davranışının altında yatan nedenleri daha iyi anlamamıza katkı sağlayarak, öğrencilerin motivasyonunu artırmaya yönelik programların geliştirilmesi için önemli bir araç sağlayacağı düşünülmektedir.
ÜNİVERSİTE ÖĞRENCİLERİNİN TÜKENMİŞLİK, SOSYAL DESTEK VE PSİKOLOJİK İYİ OLUŞLARI İLE İSTEMSİZ ERTELEME EĞİLİMLERİ ARASINDAKİ İLİŞKİNİN İNCELENMESİ
Keywords: Social and Humanities Education (Excluding Economics; Business and Management); Sosyal ve Beşeri Bilimler Eğitimi (Ekonomi; İşletme ve Yönetim Hariç)